Application Of Complementary Therapy With Fenugreek Seed Tea (Klabet) To Increase Breast Milk Production In Langkapura District, Bandar Lampung City, 2023 - Mega Silfia Sari; Ninik Indayani (International Journal of Health and Pharmaceutical (IJHP), 2024)
Background: Exclusive breastfeeding coverage in Indonesia in 2019-2020 decreased from 67.74% to 56.9%. This is caused by several problems, both maternal and baby problems. Babies who are not exclusively breastfed are very susceptible to diseases such as respiratory tract infections (ARI), diarrhea, severe intestinal problems in premature babies, decreased Intelligence Quotient (IQ) (Wijayanti, 2015). Therefore the author is interested in conducting research on "Therapeutic Application Complementary with Fenugreek Seed Tea (Klabet) to Increase Breast Milk Production in Langkapura Village, Bandar Lampung City in 2023.” Research Objective: To determine the effectiveness of applying complementary therapy of Fenugreek seed tea (Klabet) to increase breast milk production in breastfeeding mothers. Research Method: This study used an independent t test research design with a population of 30 breastfeeding mothers and the sample for this study used the total population. Data techniques use computer program statistical calculations. Research Results: In the experimental group 93.3% of respondents were aged 21-35 years, 66.7% had a high school education, 80.0% were unemployed and 53.3% were multiparous, while in the control group 100.0% were aged 21-35 years old, 60% had a high school education, 66.7% did not work and 53.3% were primiparous. In the experimental group the pre test average was 4.47 and the post test average was 9.53. Meanwhile, in the control group, the pre-test average was 4.07 with the post-test average being 6.93. Conclusions and Recommendations: Based on the results of research using an independent t test, it was found that Ho was rejected, which means there was an effect of fenugreek seed tea on breast milk production in breastfeeding mothers in Langkapura Village, Bandar Lampung City in 2023.